Diatom-based reconstruction of Holocene hydrological changes along the Colorado River floodplain (northern Patagonia, Argentina) - Fayó, Rocío (2018)
Diatom assemblages recovered from a Colorado River delta core in northern Patagonia, Argentina were analyzed in order to assess past environmental conditions. A total of 35 samples were selected from a 172-cm core extracted 37 km from the mouth (39°36′19.6″S; 62°29′26.1″W). One-hundred and thirty-eight taxa were recognized and grouped according to life forms. Two diatom zones were identified by cluster analysis. At the base of the sequence, the Diatom Zone I (DZI; 4132 ± 35 − 2919 ± 27 14C yr BP), consisted of clays, and was characterized by assemblages dominated by aerophilous and benthic taxa and chrysophyte stomatocysts, which led to inferences of a sedimentary environment corresponding to a pond experiencing dry periods. The upper section (DZII) was dominated by fine sands and silts encompassing the last ~ 150 yr with abundant planktonic and tychoplanktonic diatoms. Benthic diatoms were abruptly replaced by planktonic forms in this zone indicating a shift to deeper waters. These results characterize the meandering dynamics of a deltaic system. During the Mid-Holocene, more arid periods would have favored the deactivation of meanders and the formation of riverine and oxbow wetlands. In Late-Holocene and historical times, more humid conditions and the hydrological system across the floodplain reactivated the paleochannel. Today, the dominant diatom species are brackish/freshwater fragilaroids. A non-multidimensional scaling analysis showed a lack of analogy between fossil and modern samples. The change in diatom floras in recent historical times was attributed to anthropogenic disturbances, a consequence of the regulation of the river flow. This regulation is evidenced by less discharge, morphological modifications in the floodplain and increased salinity in the last decade.